PENGARUH PARTISIPASI PENGANGGARAN TERHADAP SENJANGAN ANGGARAN DENGAN PENEKANAN ANGGARAN DAN KETIDAKPASTIAN LINGKUNGAN SEBAGAI PEMODERASI - Desy Pratami, A.A Sagung; Adi Erawati, Ni Made (E-Jurnal Akuntansi; Vol 15 No 2 (2016), 2016)
This study aim to determine the effect of budgetary participation on budgetary slack with budget emphasis and environmental uncertainty as moderating variables in star hotels in Badung Regency. Three star hotels and above chosen as the study location because generally in hotels with that classification utilizing budget as a management tool. The research samples consist of 104 managers at 60-star hotels in Badung, with purposive sampling method. The analysis technique used is moderated regression analysis. The results indicate that there is positive and significant effect of budgetary participation on budgetary slack. The study also shows that the budget emphasis and environmental uncertainty positively moderate (strengthen) the effect of budgetary participation on budgetary slack.
Keywords: participative budgeting, budget slack, budget emphasis, environmental uncertainty